A Humanistic Approach to Preventing Bullying: Collaboration Between School Counselors and Homeroom Teachers at Vocational High School - Lalu Ahmad Bukhari; Akhsanul In'am; Dyah Worowirastri Ekowati (Universitas PGRI Yogyakarta, 2026)
Bullying in vocational schools, which involves late adolescents with complex psychosocial dynamics, requires a holistic prevention approach. This study examines the implementation of a humanistic approach through collaboration between Guidance and Counseling Teachers and Homeroom Teachers to prevent bullying at State Vocational High School 1 Narmada, West Lombok. Using a qualitative case study design, data are collected through observation, interviews, and document analysis. The results show that structured collaboration through regular coordination meetings, informal communication, and joint interventions, such as home visits, is highly effective for early detection and case management. The humanistic approach, embodied in empathy, unconditional acceptance, and reflective dialogue, is consistently applied in counseling services and learning interactions. School policy support through the Duta Sahabat and Teman Curhat programs strengthens the creation of an inclusive and safe school climate. This collaborative model not only reduces incidents of bullying but also promotes emotional awareness, peer support, and a culture of mutual respect. This study concludes that the synergy between humanistic approaches and teacher cooperation, supported by school leadership, is an effective strategy for building a positive learning environment in vocational schools. Keywords: humanistic approach, guidance and counseling, homeroom teachers, bullying, vocational schools